2018
DOI: 10.1557/jmr.2018.352
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric materials: From micro- to nanoscale

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 159 publications
(201 reference statements)
2
42
0
1
Order By: Relevance
“…Their results showed that the largest magnetocaloric effect was witnessed at the applied field of 2 T and a temperature of 308.2 K, where a temperature drop of 12.9 K and refrigerant capacity of 135.22 J kg -1 T -1 was observed for the quenched sample. FeRh near to equimolar composition nowadays possesses one of the highest refrigerant capacities even surpassing Gd 5 Si 2 Ge 1.9 F 0.1 and MnFeP 0.45 As 0.55 alloys 40 . FeRh’s second-order transition takes place at the Curie temperature of T C = 650 K, where the phase changes from the ferromagnetic B2-phase to the γ-phase which is paramagnetic (PM).…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the largest magnetocaloric effect was witnessed at the applied field of 2 T and a temperature of 308.2 K, where a temperature drop of 12.9 K and refrigerant capacity of 135.22 J kg -1 T -1 was observed for the quenched sample. FeRh near to equimolar composition nowadays possesses one of the highest refrigerant capacities even surpassing Gd 5 Si 2 Ge 1.9 F 0.1 and MnFeP 0.45 As 0.55 alloys 40 . FeRh’s second-order transition takes place at the Curie temperature of T C = 650 K, where the phase changes from the ferromagnetic B2-phase to the γ-phase which is paramagnetic (PM).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, it is possible to note a rapidly growing interest of the scientific community in the research related to applications involving the use of magnetic nanoparticles 118 . Among these studies, a particular attention has been devoted to the magnetocaloric property of the ultra-small nanoparticles (smaller than 50 nm) used for cooling purposes as discussed in the literature 2–6,9,11–13,15,17,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of its first compound (Cu 2 MnAl), which was surprisingly ferromagnetic despite not having any “magnetic” element in its composition, more than 1500 Heusler compounds have been discovered . The research on these compounds is far from over, mainly due to their possible role as superconductors, gap tunable semiconductors (between 0–4 eV), topological insulators, thermoelectrics, magnetoelectrics, magnetocalorics, etc , …”
Section: Introductionmentioning
confidence: 99%
“…For most technological applications this is insufficient since the temperature of interest is around room temperature, quite far from the 0 K assumed in the DFT calculations. Such a problem is particularly handicapping for the case of magnetocaloric materials whose region of interest is located just around its Curie temperature, hence adding additional importance to the thermodynamic behavior of the studied system …”
Section: Introductionmentioning
confidence: 99%